Fabrication and characterization of a Cu-Pd-TNPs polymetallic nanoelectrode for electrochemically removing nitrate from groundwater. (December 2018) - Lei, Xiaohui; Liu, Fang; Li, Miao; Ma, Xuejiao; Wang, Xinghui; Zhang, Hanjun
Abstract: A novel Cu-Pd-TNPs (Copper-Palladium-TiO2 Nanopores) polymetallic nanoelectrode was fabricated, and then used to catalytically reduce dissolved nitrate in groundwater. The aim was to develop a high efficient nanoelectrode for removing nitrate from groundwater. The Cu-Pd-TNPs polymetallic nanoelectrode was fabricated by plating Pd onto a TiO2 nanoporous matrix and then plating Cu onto the layer which is previous coating. TiO2 nanopores on the Cu-Pd-TNPs electrode surface gave the electrode a large specific surface area, and the Pd and Cu nanoparticles gave the electrode a high nitrogen to hydrogen ratio and a high nitrate reduction activity. Scanning electron microscopy images indicated that the Cu-Pd-TNPs polymetallic nanoelectrode was porous with lamellar deposits. The elements on the Cu-Pd-TNPs electrode surface, identified by energy-dispersive X-ray spectroscopy, were Ti, Pd, Cu, and O. The Cu-Pd-TNPs electrode gave a high nitrate reduction rate, removing 287.3% nitrate more than that was removed by a Ti nanoelectrode under the same conditions. The optimal NaCl concentration, at which the electrode effectively removed nitrate and produced as few byproducts as possible, was determined. Nitrate was completely removed using the Cu-Pd-TNPs electrode with a Pt anode at a NaCl concentration of 0.5 g L −1, little ammonia and almost no nitrite were detected in the treated solution. Using a constant current density, temperature strongly affected nitrate removal, but the initial nitrate concentration affected the removal rate little. Maximum nitrate was removed at pH 3 when the other conditions were constant. Highlights: A novel Cu-Pd-TNPs polymetallic nanoelectrode was fabricated. The novel nanoelectrode was used for electrochemical denitrification. The novel nanoelectrode has high reduction efficiency for nitrate. Very few by-products produced when added appropriate sodium chloride.